A insustentável leveza do capitalismo “verde” - Pedro Miguel Cardoso (e-cadernos ces)
The contemporary ecological crisis has been contributing to reinvigorate the academic debate on the concept of capitalism and its relation to ecology. In this essay we will frame and explain what capitalism is and present different positions that seek answers to the question of whether or not it is compatible with the ecological sustainability of the planet. The question of economic growth as a requirement of capitalism will be addressed. We will define four groups in which the main positions can be grouped: sustainable growth, stationary economy, marxist ecology and degrowth. We will argue that overcoming the ecological crisis is not in the transition towards a supposed “green” capitalism. It is necessary to work on the construction of an ecosocialist system, promoting the transformation of the relation between human beings and between them and nature.